E-027 Mechanical Thrombectomy for Acute Ischemic Stroke in Post-surgical Patients. (29th July 2016) - Litao, M; Bhamra, H; DeSousa, K; Raz, E; Nossek, E; Favate, A; Shapiro, M; Becske, T; Nelson, P
Abstract : Introduction: Ischemic strokes in the post-surgical period may negatively impact clinical outcome. Major surgery within the previous 14 days is a relative contraindication to intravenous-tPA administration. Mechanical thrombectomy may thus become a valid treatment option. We present our experience in a series of patients who presented with a clinical stroke syndrome in the post-surgical period who underwent emergent angiography with intent to treat. Methods: This is a retrospective review of patients who were treated from January 2012 to March 2015 in our institution. Patients who had emergent angiography after presenting with clinical stroke during the post-surgical period were included. Type of surgery, clinical characteristics, imaging studies, treatment variables, and discharge modified Rankin scores were collected. Results: 15 patients had emergent angiography in the post-surgical period. The mean age is 68.87 years. 87% (13/15) had cardiovascular surgery, 8 (62%) of which were valvular repairs. 57% (8/14) presented in the immediate post-surgical period. The mean NIHSS was 18. Mean symptom duration from time last known well was 256 minutes. 10/11 (91%) had perfusion deficits on CTP. 60% (9/15) had proximal vessel occlusion while 33% (5/15) had distal occlusions, and 1 had no occlusion. Of the 9 patients with proximal vessel occlusions, 7 underwent thrombectomy with the Solitaire device achieving a 57% (4/7) TICI 2 b/3 recanalization rate. The mean mRS for all patients in the series is 3.79. Patients with TICI 2 b/3 recanalization did significantly better at discharge than those who did not, mean mRS of 1.67 vs. 5, p = 0.019. Conclusion: In our experience, emergent angiography among post-surgical stroke patients showed proximal vessel occlusion in more than half of patients, making them potential candidates for mechanical thrombectomy. Those who achieved TICI 2 b/3 recanalization performed clinically better than those who did not. This may indicate the potential benefit of mechanical thrombectomy among post-surgical stroke patients. The overall lower recanalization rates in this cohort may reflect atypical clot characteristics encountered in post-surgical patients and would be an interesting avenue for further investigation. Disclosures: M. Litao: None. H. Bhamra: None. K. DeSousa: None. E. Raz: None. E. Nossek: None. A. Favate: None. M. Shapiro: 2; C; Covidien. T. Becske: 2; C; Covidien. P. Nelson: 2; C; Covidien.